Strategi Pembelajaran Mata Kuliah Pemahaman Wacana Bahasa Jepang (Dokkai) dengan Metode Komprehensif Terintegrasi - Fajria Noviana; Akhmad Saifudin (Japanese Research on Linguistics, Literature, and Culture, 2021)
Dokkai is a Japanese text reading comprehension course. In practice, students learning Japanese have difficulty understanding the contents of the text. This difficulty, in some cases, was caused not only by their weakness in understanding dokkai material, but also because of their lack of knowledge about how to learn dokkai. In order for the purpose of understanding reading to be achieved, learners must be able to optimize their knowledge and skills in reading such as good understanding of Japanese characters, vocabulary, grammatical mastery of Japanese, topics, and knowing dokkai learning methods and strategies. This can be achieved if the learning strategy can cover all the things needed in teaching dokkai. Through literature studies and surveys on the difficulties and desires of learners in teaching dokkai, this paper proposes a learning strategy called an integrated comprehensive learning strategy.